Impact of AI on the World of Finance - Khanal, Dudhiram (Journal of Rapti Babai Campus, 2025)
This paper delves into how Artificial Intelligence (AI) is changing the landscape of the financial world. AI technologies, including machine learning and predictive analytics, are helping financial institutions make smarter decisions, operate more efficiently, and offer better services to customers. From automating stock trades and detecting fraud to improving risk management and creating personalized financial solutions, AI is making its mark. The ability to quickly analyze vast amounts of data has led to more accurate market predictions and better investment strategies. However, with these advancements come challenges, such as ethical concerns, job displacement, and the need for stronger data protection. This study aims to explore how AI is shaping finance today, its potential future impact, and the steps needed to address the risks and ensure responsible use.